Analisis Perubahan Laba Kotor (Gross Profit) pada P.R. Kembang Jati Kudus - Rozaq, Khoirur (BISMA (Bisnis dan Manajemen), 2018)
The company’s performance usually seen from the financial aspect is generated by analyzing the financial statements of the income statement. Analyzing the income statement aims to determine the extent to which the corporate earnings to the owner for a certain period. Analyzing the income statement can be carried out by analyzing changes in gross profit. This analysis is useful to determine the level of efficient and effective company in business. The lower gross profit continuously can be caused by changes in the selling prices of products, changes in the price of production and other costs to be incurred by the company every year, causing a decrease in gross profit, which in turn lead to acceptance of the company’s profits are reduced or even loss. Income is mainly influenced by three factors are interrelated to one another, namely sales volume, sales prices, and production costs. The research objective is to analyze the changes in gross profit (Gross Porfit), to assess the factors causing the change in gross profit PR Kembang Jati and search efforts to maintain the increase in gross profit to the company’s performance can be improved.